PEMANFAATAN TEKNOLOGI INFORMASI PADA PEMBELAJARAN IPA SD - Agung Wijayanto; Dian Hidayati (Journal of Education and Teaching (JET), 2024)
This study aims to examine the utilization of information technology in science education at the elementary school level during the Covid-19 pandemic. The pandemic, which has affected Indonesia and various other countries, has necessitated a shift to online learning to ensure the continuity of the educational process. In this context, the Minister of Education and Culture has instructed that learning should continue by leveraging information technology. E-learning has emerged as a key solution for facilitating education. This research employs a qualitative approach using literature review and interview methods to interpret and explain the object of study, which is the analysis of the utilization of information technology in elementary school science education. The findings indicate that the use of information technology in elementary school science education can be effectively implemented if strategies and approaches are aligned with the Basic Competencies (Kompetensi Dasar, KD). These results demonstrate that with proper adaptation, information technology can effectively support the educational process, even under challenging conditions such as the pandemic.